The Importance of Knowledge Management in Secondary Vocational Education Organizations in Greece - Zygouris, Fotios; Papadopoulou, Sofia (International Journal of Scientific Research and Management (IJSRM), 2023)
In recent years, knowledge management has increased in popularity as a management tool, as well as a new research field. Most organizations realize that "knowledge" is a strategic resource that can provide them with a sustainable competitive advantage and help them to achieve long-term organizational goals. Based on this, organizations attempt to use knowledge management to promote innovation, to improve organizational efficiency also to accelerate the creation and exchange of knowledge. The purpose of this paper is to present the importance of knowledge management in Greek vocational education. Essentially, it will study and try to highlight the way Vocational High Schools (VΗC), which are being secondary vocational education organizations, to attempt to manage knowledge in an effective way, also the knowledge management practices that can be useful in such an environment. The conclusions highlight the important elements of knowledge management in technical vocational education organizations.